MODIFIED METHOD OF LAPAROSCOPIC LONGITUDINAL GASTRIC RESECTION IN SURGICAL TREATMENT OF PATIENTS WITH METABOLIC SYNDROME AGAINST THE BACKGROUND OF GASTROESOPHAGEAL REFLUX DISEASE - С. Давлатов; Б. Хамдамов; М. Хакімов; А. Хамдамов; І. Хамдамов (Неонатологія, хірургія та перинатальна медицина)
Obesity and metabolic syndrome represent significant risk factors for the development of cardiovascular diseases, which are statistically the leading cause of mortality [1]. This underscores the necessity of conducting scientific research on pathologies characterized by a comorbid course [2].